الحد من السلوكيات المهنية المسيئة للطبيب من منظور الشريعة الإسلامية والمواثيق الدولية الطبية - Sami Khalaf Salim Al-Bazirat
Human beings are honored while being created , before and after getting down to the Earth in the Shariah, and the international conventions approved his dignity. No human is allowed to abuse the dignity of another human and cause harm to him. Furthermore, scientific development positively affected the different life domains; however, it didn't lack shortcomings. It had positive effects and developments on the medical domain, in terms of the medical procedures; however, these procedures paved the way for certain behaviors that are practiced in secret and in public , which adversely affect the doctor's reputation and cause harm to those dealing with him, These behaviors also contradict the provisions of the Shariah and the international conventions. Indeed, such behaviors entail demonstrating the justifications in order to reduce them within the domain of this study, clarifying the characteristics that reduce such behaviors according to the Shariah and the international conventions as well as educating those dealing with the doctor about the doctor's duties before and during the medical procedure , in addition to the objective of the therapy; therefore, the patient is informed about his rights in Islam and the international levels, where lack of commitment to those behaviors entails liability. In order to achieve the study objectives, the researcher used comparative analytical descriptive approach to demonstrate that the Shariah and the international conventions reduced the professional behaviors that cause harm to the doctors with a relative difference between them. We noticed that the Shariah was better in terms of clarification, details, inclusion of topics, preventive procedures and coordination in its contexts that are free of contradiction in relation to reducing those behaviors. Therefore, it included a certain arrangement of liability different from that included in the international conventions, in that the contexts of the international conventions were public in nature and could lead to a contradiction in the rights cited in them. Additionally, the international conventions included constraints that could be explained in broad terms, and that has the potential of reducing the rights given to the individual in those conventions; therefore, there is a lack of liability in case those rights weren't taken into account. Accordingly, the Shariah was better even in protecting the human rights which it agreed upon them with the international conventions.